O skate na cultura corporal de movimento: aspectos evolutivos e sociais - Coelho, Pedro Casasco Ribeiro [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Skateboarding gets practitioners and followers all over the world and it's still growing. Thus performing a detailed analysis of its tracks becomes exciting. This study has a purpose of investigation about the evolution of the skateboard as a leisure activity and as a sport, supported by historical and social factors analysis that influenced their growth. Furthermore to understand the sport history and its influence in the socialization process, and also in the insertion of individuals in a social context within the body movement culture. The methodology used in this study was based on a literature review, analyzing articles, books, documents, websites and reports of the genre. It was concluded that the practice of skateboarding is unique and it's promoted to be and to have self identity and it is directly related to an activity that is characterized as free and creative without any molded identity. And also promote the insertion of this kind of skateboarding as a universal phenomenon about the body movement seeking social interactions in different educational views through a sharing attitude

O skate é uma modalidade que ganha praticantes e adeptos no mundo inteiro e que cresce a cada dia. Torna-se, então, instigante a realização de uma análise mais minuciosa de suas vertentes. Sendo assim, o objetivo deste trabalho é investigar a evolução do skate como atividade do contexto do lazer, e como modalidade esportiva, com apoio de análise histórico-social dos fatores que influenciam seu crescimento. Além disso, buscar compreender a trajetória e a influência que a modalidade possui no processo de socialização, inserção dos indivíduos num contexto social, dentro da cultura corporal do movimento. A metodologia utilizada neste trabalho se pautou numa revisão de literatura sobre o assunto, analisando artigos contidos em base de dados, livros, documentos, sites e reportagens do gênero. Concluiu-se que a prática do skate é singular e se justifica por ser e ter auto identidade e diretamente associada a uma atividade que se configura como livre, criativa, sem qualquer identidade dirigida. E que essa configuração do skate como fenômeno universal do uso do corpo e do movimento objetivando interações sociais possa ser inserida nas diferentes visões educacionais por meio de um compartilhamento de atitudes
Keywords: Esportes - Aspectos sociológicos; Skate (Esporte); Socialização